An epic of the sea: between Eliot and Pagliarani (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2020)
Water, especially in the image of the sea, is one of the central motifs of Elio Pagliarani's Ballata di Rudi. This paper aims at demonstrating the influence of T.S. Eliot's The Waste Land in the structuring of Pagliarani's work and in the fine-tuning of the aquatic theme. The possibilities (and ways) of the epic in 20th century poetry will be discussed in order to propose an ecologist reading of Pagliarani's Ballata.
Keywords: Elio Pagliarani, T.S. Eliot, La Ballata di Rudi, epic, ecology